The Detection of Extensively Drug-Resistant Proteus mirabilis Strains Harboring Both VIM-4 and VIM-75 Metallo-β-Lactamases from Patients in Germany - Moritz Fritzenwanker; Jane Falgenhauer; Torsten Hain; Can Imirzalioglu; Trinad Chakraborty; Yancheng Yao (Microorganisms)
Proteus mirabilis is a well-known opportunistic pathogen predominantly associated with urinary tract infections. It exhibits natural resistance to multiple antibiotics, including last-resort options like colistin. The emergence and spread of multidrug-resistant P. mirabilis isolates, including those producing ESBLs, AmpC cephalosporinases, and carbapenemases, are now more frequently reported. The most common carbapenemase types found in P. mirabilis are KPC-2, IMP, VIM, NDM, and OXA-48. We sequenced the genomes of three carbapenem-resistant P. mirabilis isolates harboring both blaVIM-4 and blaVIM-75 from Germany using both short-read and long-read sequencing techniques. We found that the isolates were only distantly related genetically. Both blaVIM-4 and blaVIM-75 genes were located on a class I integron, which in two cases was located on the chromosome and in one case on a plasmid. This is the first report on the complete genomes of P. mirabilis strains harboring a rare genetic element encoding both blaVIM-4 and blaVIM-75. Our results emphasize a key role for class 1 integrons in the transmission of VIM carbapenemases in P. mirabilis.